Step Responses of Tuned Conventional Controller for a Three Tank Liquid Filled System - Kunal Chakraborty; Rahul Dev Basak; Dipak Kumar Dutta (Institute of Advanced Engineering and Science, 2014)
In this paper modeling of a temperature measuring tank system has been done and then a tuned PID Controller have been used for controlling the step responses of the system. The proposed system extends to a three tank system & each tank has same amount of liquid. The results of computer simulation for the system with Proportional, Integral and Derivative (PID) Controllers are shown here using MATLAB( R2007b) software.